Project management under risk - Valentina Yu. Shalashnikova, Olga V. Rogach, Tatyana M. Ryabova, Elena V. Frolova, Tatiana V. Bogacheva, (Opción, 2020)
The paper analyzes the current aspects of project management under risk. The empirical base of the research is the advertising agency LLC “22 VEK PLUS”. To improve the efficiency of project management in an advertising agency, it is advisable to introduce a matrix (mixed) structure. It was found that spontaneous formation of project teams becomes one of the problems in the company’s work when implementing advertising activity. This leads to uncoordinated project implementation: the lack of common terminology and a common understanding of the project management principles, also the lack of a clear delineation concerning the areas of responsibilities.